Platelet-derived biomaterials-mediated improvement of bone injury through migratory ability of embryonic fibroblasts: in vitro and in vivo evidence - Chou, Yen-Ru (Aging (Albany NY), 2021)
Bony injuries lead to compromised skeletal functional ability which further increase in aging population due to decreased bone mineral density. Therefore, we aimed to investigate the therapeutic potential of platelet-derived biomaterials (PDB) against bone injury. Specifically, we assessed the impact of PDB on osteo-inductive characteristics and migration of mouse embryonic fibroblasts (MEFs). Osteogenic lineage, matrix mineralization and cell migration were determined by gene markers (RUNX2, OPN and OCN), alizarin Red S staining, and migration markers (FAK, pFAK and Src) and EMT markers, respectively. The therapeutic impact of TGF-β1, a key component of PDB, was confirmed by employing inhibitor of TGF-β receptor I (Ti). Molecular imaging-based in vivo cellular migration in mice was determined by establishing bone injury at right femurs. Results showed that PDB markedly increased expression of osteogenic markers, matrix mineralization, migration and EMT markers, revealing higher osteogenic and migratory potential of PDB-treated MEFs. In vivo cell migration was manifested by expression of migratory factors, SDF-1 and CXCR4. Compared to control, PDB-treated mice exhibited higher bone density and volume. Ti treatment inhibited both migration and osteogenic potential of MEFs, affirming impact of TGF-β1. Collectively, our study clearly indicated PDB-rescued bone injury through enhancing migratory potential of MEFs and osteogenesis.